The World in arms : AD 1900-1925 - Time-Life Books (Amsterdam : Time-Life Books, 1990)
1. World History--AD 1900-1925. 2. World War I.
Includes bibliographical references and index
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: Military history, Modern -- 20th century; Revolutions -- History -- 20th century